Report and Analysis on Ayatullah Jawadi Amuli’s Viewpoint about the Ethical Relativism - Mustafa Salatin; Muhsen Jawadi (اخلاق وحیانی)
Ascription and moral relativism are of important issues throughout the history of philosophy. Some people impressed by the findings of cultural differences; societies; customs; And even personal tastes, with rejecting every kind of generalism and ascription in the scope of ethics’ rules, have inclined toward relativism. On the other hand, some people consider relativism unlike the intellectual findings and believe in it to the detriment of individuals and general interest of the society. Relying on religious beliefs and intellectual comprehensions, Muslim philosophers believe that ethics’ rules originate from reality and they don’t believe in relativism. Grand Ayatullah Jawadi Amuli, commentator of exalted theosophy and Islamic philosopher, with respect to human knowledge and the methods to obtain it, and totality and immortality of moral principles and precepts, has rejected any kind of moral relativism or even relativism in anthropology, and He has proven being scientific and discursive of moral principles referring to human experience on recognizing moral precepts. This paper tries to describe the Exalted Theosophist’s reasoning on criticizing the fundamental components of moral relativism, and also His arguments on Ascription and Totality demonstrate the true basis of moral principles and precepts.